Causas de las dificultades de aplicación del teorema de Arquímedes por los alumnos de Enseñanza Media - Fernández Fernández, J. M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In order to find out the reasons why the students of 2nd year BUP have so much trouble to solve exercises by applying Archimedes' theorem, we have presented them with five questions. From their answers we learn that most of them do not relate the volume of displaced liquid to that of the submerged body, but to its mass or weight. For most of the students the more mass or weight of the submerged body, the more volume of displaced liquid.